Applied architecture patterns on the Microsoft platform : work with various Microsoft technologies using applied architecture patterns - Dovgal, Andre; Noriskin, Gregor; Olechko, Dmitri (Professional Expertise Distilled, 2014)
Presented in a scenario-driven tutorial way, we lead you through fictitious example problems and present you with the best solutions. This book is intended for architects, developers, and managers who need to improve their knowledge of the Microsoft application platform. This book will appeal to anyone, especially consultants, who want to get up to speed on selecting the most appropriate platform for a particular problem. A good understanding of the general Windows platform and development technologies would be helpful.